Determination of optimum insulation thickness in submarines - Durmaz, Savas; Batur Colak, Andac; Mercan, Hatice; Dalkilic, Ahmet Selim (YILDIZ TECHNICAL UNIV, 2023)
One of the most effective ways to save energy for cooling and heating applications is thermal insulation. Because of this, determining the ideal insulation thickness is a popular topic for publications. The purpose of this study is to determine the appropriate insulation thickness needed for a submarine's external construction while it is cruising in various locations. Since seawater makes up a submarine's external environment, situations involving five distinct seawater temperatures from around the globe have been studied. There are five of them: the Mediterranean, Marmara, Aegean, Black Sea, and Sakhalin, which is in the North Pacific Ocean and has the coldest seawater on earth. By using the idea of degree-days, the annual cooling and heating needs of submarines in various regions have been computed. Based on life cycle cost analysis, optimization has been accomplished. In the beginning, the results of a study published in the literature supported the calculation methods utilized. The use of insulation materials such as rock wool, glass wool, polyurethane, expanded polystyrene, fiberglass, and foam glass, as well as fuel oil to run the generator, has been taken into account in a number of calculations, including the best insulation thickness, annual savings value, annual energy cost, and payback period. The findings indicate that depending on seawater temperatures and insulation materials, the ideal insulation thicknesses range between 2 and 12 cm, energy savings between 8.5% and 90%, and payback periods between 1.1 and 10 years.
Keywords: Energy Saving; Life-Cycle Cost Analysis; Optimum Insulation Thickness; Submarine; Thermal Insulation; EXTERNAL WALLS; BUILDING WALLS; CLIMATE ZONES; RESPECT; FUELS; Thermodynamics